What people close to death say about euthanasia and assisted suicide: a qualitative study. - Chapple, A; Ziebland, S; McPherson, A; Herxheimer, A (2006)
OBJECTIVE: To explore the experiences of people with a "terminal illness", focusing on the patients' perspective of euthanasia and assisted suicide. METHOD: A qualitative study using narrative interviews was conducted throughout the UK. The views of the 18 people who discussed euthanasia and assisted suicide were explored. These were drawn from a maximum variation sample, who said that they had a "terminal" illness, malignant or non-malignant. RESULTS: That UK law should be changed to allow assisted suicide or voluntary euthanasia was felt strongly by most people. Those who had seen others die were particularly convinced that this should be a right. Some had multiple reasons, including pain and anticipated pain, fear of indignity, loss of control and cognitive impairment. Those who did not want to be a burden also had other reasons for wanting euthanasia. Suicide was contemplated by a few, who would have preferred a change in the law to allow them to end their lives with medical help and in the company of family or friends. The few who opposed a change in UK law, or who felt ambivalent, focused on involuntary euthanasia, cited religious reasons or worried that new legislation might be open to abuse. CONCLUSION: Qualitative research conducted on people who know they are nearing death is an important addition to the international debate on euthanasia and assisted suicide. Those who had seen others die were particularly convinced that the law should be changed to allow assisted death.